The long-distance dispatch between Lydia Goldblatt & Julie Graham-Chang - Ignatow, Amy (New York : Amulet Books, 2011)
Two best friends are separated when Lydia's mother takes a job in London for six months, where Lydia tries to adjust to being an American in an English school and Julie has to deal with the cliques of junior high and a group of troublemakers who want to take her under their wing.
Keywords: Best friends -- Juvenile fiction; Fiction